Razvoj kirurških metod rehabilitacije govora po laringektomiji - Šifrer, Robert (Rehabilitacija (Ljubljana), 2018)
Restitution of the ability to speak is the main goal of the rehabilitation process of patients after laryngectomy. This has been the aim of physicians since the first performance of laryngectomy. The main principle of the rehabilitation is redirection of the exhaled air from the upper airways into the upper alimentary tract what leads to vibrations in this location and consequently to the production of voice. The article is limited to the development of surgical methods of rehabilitation of speech after laryngectomy. The patient can use only pseudo-whisper after laryngectomy. The surgically created shunt between upper airways and upper alimentary tract and inserting various valves (prostheses) into the shunt enables the patient to speak loudly soon after laryngectomy.
Keywords: govor; internal tracheo-pharyngeal prosthesis; notranja traheo-faringealna proteza; pseudo-whisper; psevdo-šepet; Rehabilitation of Speech and Language Disorders; speech; tracheo-esophageal fistula; traheo-ezofagealna fistula